Measuring the achievements of smart economics in the smart village program in Lampung Province 2020-2024 - Endriyono , Endriyono; Gunarto, Toto; Murwiati, Asih (Goodwood Publishing, 2025)
Purpose: This study aims to measure the impact of Smart Village dimensions on rural community welfare in Lampung Province from 2020 to 2024, focusing on the Smart Economy pillar and its integration with digital transformation and technosociopreneurship. Methods: A quantitative approach was applied using multiple linear regression (Ordinary Least Squares) on data from 70 Smart Village loci across four districts. The independent variables include Smart People, Smart Governance, Smart Mobility, Smart Environment, Smart Living, and Smart Economy, while the dependent variable is community welfare. Instrument validity and classical assumption tests ensured model reliability. Results: All six Smart Village dimensions significantly and positively affected community welfare, with Smart People having the highest coefficient (0.8489). The model showed strong explanatory power (R² = 0.9535) and passed all classical assumption tests. Smart Economy initiatives—digitalization of MSMEs, inclusive market access, and technology-driven entrepreneurship—directly enhanced household income, job creation, and local growth. Conclusion: Implementation of Smart Village principles, especially smart economic transformation, significantly improves rural welfare. Digital innovation, good governance, and community capacity-building strengthen service quality, economic inclusion, and sustainability. Limitation: The study is limited to Smart Village implementations in Lampung Province, excluding interregional comparisons and long-term behavioral aspects. Contribution: This study provides empirical evidence of Smart Village effectiveness in rural development, supporting policy formulation on digital infrastructure, entrepreneurship training, and stakeholder collaboration, while offering a replicable model for evaluating Smart Village outcomes in other regions.